Investigation of electro-coagulation process for the reduction of total suspended solids from palm oil mill effluent / Firdaus Ghazali - Firdaus, Ghazali (2013)
Palm oil mill effluent (POME) is characterized by high chemical oxygen demand (COD) and total suspended solids (TSS). This leads to difficulties in their treatment by conventional treatment methods thus failing to meet the minimum allowable discharge. The attractive option incorporating a pre-treatment process to reduce the values of these parameters is electrocoagulation (EC) technology. In this study, the EC process of POME (19,000 – 21,000 mg/L of TSS and 60,000 – 63,000 mg/L of COD) was investigated utilizing aluminum electrode. The effects of initial pH, current density, stirring speed, temperature and operating time on the removal efficiency of TSS and COD were examined. The experiments were conducted batch wise using 400 ml of POME per batch as the reaction mixture volume. Removal of 85.3 % of the wastewater TSS and 35.7 % of the COD were attained at the optimal operating conditions. This corresponded to the initial pH of 6, current density of 120 A/m2, stirring speed of 100 rpm, temperature of 27 °C and operating time of 15 minutes. Limiting the current density favors low heat generation and excessive oxygen evolution during the treatment. The formations of flocks have the potential to break and release residue particles into the POME at higher stirring speeds. Chemical coagulation (CC) also conducted on POME as comparative study to EC process. As a result, EC was more efficient in removing TSS and COD through efficient Al3+ and operating time consumption. In conclusion, the study demonstrated that EC process is able to treat POME to the allowable discharge limit effectively through reduction of TSS and COD at the initial stage and it is suitable as an alternative preliminary process for POME treatment.